Penerapan Bandwidth Management Untuk Dynamic User Pada Mikrotik Menggunakan Per Connection Queue (PCQ) - M. Agus Syamsul Arifin (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2018)
Simple Queue is a solution that is most convenient for use in performing Bandwidth Management by entering the amount of bandwidth that will be used and the IP address to be restricted bandwidth. Problems will arise if it turns out the number of users that there is a user with a considerable amount. Not to mention if the User is Dynamic. Users can be connected or disconnected at will the user. It would be very inconvenient if you had to make Simple Queue individually for each user. One way that can be used to overcome this problem is by PCQ (Per Connection Queue), PCQ is one way of doing that is easy enough bandwidth management where PCQ works with an algorithm that will divide evenly bandwidth to a number of users are active. Ideal PCQ be applied if the difficulty in determining the setting Bandwidth Bandwidth per User. How it works is by adding PCQ sub-queue, based on a certain classification by entering the amount of their bandwidth Upload and Download. PCQ split evenly banwidthkesetiap User